Pengaruh Ekspor, Impor, Cadangan Devisa, Suku Bunga Bank Sentral dan Tingkat Inflasi Nilai Tukar IDR terhadap USD dari Januari 2019 hingga Desember 2021, dibandingkan dengan Studi dari Januari 2011 hingga Desember 2013 per Kasus Dari Indonesia: The Influence of Export, Import, Foreign Reserve Currencies, Central Bank Rate of Interest and Inflation Rate on IDR Exchange Rate to USD from January 2019 to December 2021, Compare to Study from January 2011 to December 2013 a Case from Indonesia. - Sunardiyaningsih, Siti Purnami; Pradiptha , Anindya Putri (KRESNA: Jurnal Riset dan Pengabdian Masyarakat, 2022)
The aim of this research is to study the influence of independent variables to the fluctuation of IDR exchange rate to USD. Those independent variables are export, import, foreign reserve currencies, Central Bank rate of interest and inflation rate. The population is Indonesia’s economics and the sample is data for three years. Data was analyzed by using multiple regression, the sources of data are from Central Bank (Bank Inonesia) and Central Bureau of Statistics Indonesia. Research objectives are to determine the influence of export, import, foreign reserve currencies, Central Bank rate of interest and inflation rate. The result of this research shows that import make the IDR/USD exchange rate depreciate .BI Rate, foreign reserve currencies significantly influence to the rate of exchange make the Rupiah appreciate. Export and Inflation rate does not influence the IDR/USD exchange rate, because inflation rate in Indonesia is creeping inflation. Compare to the previous study (2014) independent variables which are influence to exchange rate are export, import, reserve, rate of interest